Іnformation and communication technologies and their integration in the teaching process regulations - Oksana Chekan (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the role and place of ICT in the educational process of modern preschoolinstitutions have been outlined. The ways of integration the ICT into the educational process ofpreschool institutions have been specified. Psychological and educational literature about ICTin upbringing process have been analyzed. Theoretical foundations of information andcommunication technologies and their integration into the educational process of preschoolshave been studied. The key goals and objectives of the problem have been determined. Theterms of use the ICT in the preschools have been grounded. The didactic capabilities ofmultimedia technologies have been verified. Computer games as a factor of child'sdevelopment have been determined. Key words: information technologies, information and communication technologies,information society, computer games, multimedia.